Aligning social concerns with information system security: A fundamental ontology for social engineering. Issue 104 (February 2022) - Li, Tong; Wang, Xiaowei; Ni, Yeming
Abstract: Along with the rapid development of socio-technical systems, people are playing an increasingly important role in information system and have actually become an essential system component. However, unlike technology-based attacks that have been investigated for decades, social engineering attacks have not been efficiently addressed. In particular, due to the interdisciplinary nature of social engineering, there is a lack of consensus on its definition, hindering the further development of this research field. In this paper, we propose a comprehensive and fundamental ontology of social engineering based on a systematic review of existing social engineering taxonomies and ontologies in order to provide a theoretical foundation for social engineering analysis. The essential contributions of this paper include: (1) propose a comprehensive ontology of social engineering and precisely specify ontological definitions of its essential concepts based on Situation Calculus; (2) enumerate and summarize a set of social engineering techniques and present their fine-grained classification based on the proposed ontology; (3) incorporate psychology and sociology knowledge into social engineering analysis, encapsulating such knowledge in terms of a formalized ontology. We have evaluated our ontology based on a set of real social engineering attacks, the results of which show the usefulness of our proposal. Highlights: A review of existing social engineering ontologies. A proposal of a unified set of concepts of social engineering. A proposal of ontological definitions of social engineering based on Situation Calculus. A presentation of fine-grained classification of social engineering techniques, incorporating psychology and sociology knowledge into social engineering analysis. A formalization of social engineering ontology using Description Logic.